An Unusual Foreign Body in the Maxillary Antrum: A Case Report and Pertinent Review of Literature - Date, Amit S; Padhye, Mukul N; Shah, Vaibhav D; Vandekar, Mukund J (Journal of Orofacial Research, 2014)
Maxillary sinus is the largest of the paranasal sinuses and occupies the body of Maxilla. It is pyramidal in shape with base toward lateral wall of nose and apex directed laterally into thezygomatic process. It is roof is formed by the floor of the orbit and grooved by infraorbital nerve. Foreign bodies may present in the paranasal sinuses through a variety of traumatic andiatrogenic events. We describe a case where a sharp foreign body penetrated into the maxillary sinus. We used the open surgical approach, for the removal of sinus foreign body.